Current Situation about Dispute of Bone Convergence - Zhuile WU; Zhen HE (康复学报)
"Eight convergent points"is originated from a group of definite points in a book called"Nanjing", and is emphasised by physicians of successive ages since ancient times."Eight convergent points"is commonly used nowadays. Bone convergence is one of"Eight convergent points", but there is a dispute about whether bone convergence is Dashu (BL11) or Dazhui (DU14) acupoint. Through consulting literature and analyzing theory of modern physicians, then summarying the viewpoints from application of ancient Chinese characters, meridian theory, clinical application, anatomical position and animal experiment, the results show that DU14 is more appropriate as a bone convergence acupoint. It will provide help to clinical acupoints selection.